Selected Issues Relating to Modeling of Objects and Clothes in the Creating Visualization of Mechanical Hazard during Machine Operation. (25th January 2022) - Filipek, Dariusz
Abstract : This paper presents selected IT tools of 3ds max software functions useful to create visualization of mechanical hazard, especially in object and character modeling aspect. This visualization was elaborated in Central Institute of Labour Protection-National Research Institute. This visualization was elaborated like multimedia OHS training materials from machines operators, OSH employees and employers of mechanical plants, and all institutions of metal machining industry.